Synthesis and In Vitro Antimicrobial Evaluation of New 1,3,4-Oxadiazoles Bearing 5-Chloro-2-methoxyphenyl Moiety - Prasanna Kumar, Basavapatna N. (Hindawi Publishing Corporation, 2013)
A series of new 1,3,4-oxadiazole derivatives, 4(a–h), containing 5-chloro-2-methoxy benzohydrazide moiety were synthesized by the reaction of 5-chloro-2-methoxybenzoate with different aromatic carboxylic acids. These newly synthesized compounds were characterized by FT-IR, (1)H NMR, mass spectra, and also by elemental analysis. All the newly synthesized compounds were screened for their antibacterial and antifungal activities. Antimicrobial studies revealed that compounds 4c, 4f, and 4g showed significant activity against tested strains.